Victor Serge en México, 1941-1947 - Urías Horcasitas, Beatriz (El Colegio de México, A.C., 2021)
This article examines the transformation of Victor Serge’s political positions during his exile in Mexico from 1941 to 1947. During this period, through a critique of Soviet and Nazi totalitarianism, Serge reformulated orthodox communism in favor of a renewed socialism that included the principles of democracy and freedom. This provoked a schism within the Socialismo y Libertad group, revealing the profound differences between Serge’s antitotalitarian critique and the anticommunist position that Julián Gorkin would move towards in the 1950s. Using sources such as Serge’s diary in Mexico and publications such as Análisis. Revista de Hechos e Ideas (1942) and Mundo (1943-1945), this article argues that this redefinition of socialism was deeply influenced by Serge’s exchanges with a small circle of German-speaking writers, doctors and psychoanalysts whose anti-Stalinism put them in constant tension with the communist exiles who also found themselves in Mexico. Serge’s critique of orthodox communism includes elements of Marxist thought, literature and psychoanalysis, introducing the variables of subjectivity and the unconscious in the analysis of political and social processes. The coincidence of these perspectives in the framework of a political reflection on the consequences of World War II is a distinctive feature of Serge’s thinking during the last stage of his life.